Emergency Pregnancy with Severe Preeclampsia and Total Atrioventricular Block In A 28-Year-Old Woman - Muhamad Nofa Cholili; Yahya Irwanto (Universitas Muhammadiyah Surabaya, 2025)
The co-occurrence of preeclampsia with bradycardia due to total atrioventricular block (TAVB) during pregnancy is a rare yet severe phenomenon. There is limited literature available on this specific combination. This case report aims to contribute valuable insights by documenting the clinical presentation and management of a 28-year-old woman who is diagnosed with severe preeclampsia and total atrioventricular block during pregnancy. A 28-year-old pregnant woman was referred to the emergency room with dyspnea and vaginal discharge. She had a history of cardiac issues, including atrial septal defect and total atrioventricular block. Her blood pressure was 206/129 mmHg, and a pulse rate of 67 beats per minute. Then, she was diagnosed with severe preeclampsia, hypertensive emergency, and impending eclampsia with a suspect congenital disease contributing to her atrioventricular block. The patient underwent urgent cesarean section intrauterine stabilization and received postoperative care. Postoperatively, the patient reported no further dyspnea or bradycardia. The history of salbutamol usage and the activation of plasminogen activator inhibitor-1 (PAI-1) in patients with atrial septal defects (ASD) is suspected as a potential etiological factor in the pathophysiology of preeclampsia during pregnancy. TAVB can be induced by congenital ASD. In conclusion, the use of salbutamol and activation of PAI-1 in patients with TAVB induced by ASD are suspected as potential causes of preeclampsia during pregnancy.